Kausalitas Kinerja Karyawan dengan Motivasi dan Lingkungan Kerja serta Mediator Kepuasan Kerja - Triwinata Sutedjo, Yonathan; Setiawan, Rony (Lentera Ilmu Nusantara, 2024)
Employee performance always plays a very important role in the survival and sustainability of every company over a long time horizon. Based on literature and empirical reviews, it is known that optimal employee performance can be determined or caused by having positive work attitudes. Employees who have a better perception and perspective regarding work, environment, and job satisfaction tend to strive in performing and achieving work performance with an increasing trend. This research aims to investigate the cause and effect relationship between motivation and work environment on employee performance with job satisfaction as a mediator. Carried out using simple random sampling and digital questionnaire design, this research involved 86 employees of PT X, one of the largest housing project development services companies in Bandung. After applying multiple regression studies and the Sobel test, through this study, it has been proven that job satisfaction and employee performance are influenced by motivation and work environment, while employee performance is not influenced by job satisfaction and job satisfaction is not a mediator of employee performance which is caused by motivation and work environment. This research should serve as a facilitator of constructive input for wiser human resource management by the companies concerned and the development of similar studies in the future by other researchers.